Déjà vu and the feeling of prediction: an association with familiarity strength. Issue 7 (9th August 2021) - Cleary, Anne M.; McNeely-White, Katherine L.; Huebert, Andrew M.; Claxton, Alexander B.
ABSTRACT: A recent laboratory study by Cleary and Claxton [2018. Déjà vu: An illusion of prediction. Psychological Science, 29 (4), 635–644. http://journals.sagepub.com/doi/full/10.1177/0956797617743018] documented a relationship between déjà vu and feelings of premonition. During instances of retrieval failure, participants reported stronger feelings of prediction during déjà vu than non-déjà vu states, despite displaying no actual predictive ability in such instances. The present study further explored the link between déjà vu reports and feelings of prediction. Although feelings of prediction were more likely to occur during reports of déjà vu than non-déjà vu, they were not the sole defining feature of déjà vu, accounting for just over half of all reported déjà vu states. Instances of déjà vu that were accompanied by feelings of prediction were associated with greater feelings of familiarity than instances that were not. This was shown by a greater likelihood of reporting that the scene felt familiar and also by a higher rated intensity of the feeling of familiarity elicited by the scene when it did feel familiar. Though the present study was mainly descriptive in characterising the interrelations between déjà vu, feelings of prediction, and familiarity, the full pattern points toward the possibility that high familiarity intensity may contribute to the feeling of prediction during déjà vu.